2022
DOI: 10.3389/fneur.2022.735181
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Metabolism and Ischemic Cerebrovascular Disease: A Narrative Review

Abstract: Inorganic and organic nitrates are present in vivo and in vitro. Inorganic nitrate is considered a pool of nitric oxide (NO), but it can be converted into nitrite and NO through various mechanisms. It plays an important role in the regulation of complex physiological and biochemical reactions, such as anti-inflammatory processes and the inhibition of platelet aggregation, which are closely related to the pathology and treatment of cerebrovascular disease. Ischemic cerebrovascular disease is characterized by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 122 publications
(136 reference statements)
0
5
0
1
Order By: Relevance
“…Oxidative stress disturbs Nitric oxide signalling and induces inflammation. 43 Ischemic condition activates iNOS which in turn elevates nitric oxide which oxides the lipids, and protein causing cell injury. 44 In this study, the MCAO-performed rats showed increased levels of nitrate in cortex and striatum regions of the brain and also showed an increased level of lipid peroxidation confirming the cell infarct.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress disturbs Nitric oxide signalling and induces inflammation. 43 Ischemic condition activates iNOS which in turn elevates nitric oxide which oxides the lipids, and protein causing cell injury. 44 In this study, the MCAO-performed rats showed increased levels of nitrate in cortex and striatum regions of the brain and also showed an increased level of lipid peroxidation confirming the cell infarct.…”
Section: Discussionmentioning
confidence: 99%
“…In the tumour microenvironment, low to moderate levels of NO (NO) derived from tumour and endothelial cells can activate angiogenesis, promoting an aggressive phenotype. Conversely, high levels of NO derived from M1 macrophages and Th1 lymphocytes can exert an anti-tumoural effect, providing protection against cancer [1,8,15,16]. Therefore, identifying the NO equilibrium state is particularly important for ccRCC biology.…”
Section: The Disruption Of No Homeostasis In Ccrccmentioning
confidence: 99%
“…Three isoforms of NO synthetases (NOSs) are known to be involved in NO synthesis: endothelial (NOS1 or eNOS), inducible (NOS2 or iNOS), and neuronal (NOS3 or nNOS) [16,26].…”
Section: The Disruption Of No Signaling In Ccrccmentioning
confidence: 99%
See 1 more Smart Citation
“…Тому за фізіологічних умов окиснення NO до нітритів можна розглядати як безпечний шлях утилізації надлишкового NO. Проте за умов ацидозу та накопичення великої кількості речовин із високим редоксним потенціалом (НАДН відновлений, ФАДН відновлений, тощо) можливе зменшення інтенсивності окиснення нітритів до нітратів та навіть відновлення нітритів до оксиду азоту (за допомогою нітратнітритредуктазних систем) [9]. Накопичення великої кількості нітритів, особливо при наявності АФК, створює умови для нітрування (приєднання простетичної групи NO2 -) білків, що змінює їхню активність та може надати їм антигенних властивостей [10].…”
Section: результати та їх обговоренняunclassified